INVESTIGATION OF PROTEIN PATTERNS AND ANTIOXIDANT ACTIVITY OF COLLAGEN HYDROLYSATES FROM SKIN OF FAN-BELLIED LEATHERJACKET Monacanthus chinensis BY VARIOUS ENZYMES - Ky, Pham Xuan; Vy, Phan Bao; Ha, Dao Viet; Hy, Le Ho Khanh; Hong, Nguyen Thu; Thiet, Doan Thi; Anh, Nguyen Phuong (Vietnam Journal of Marine Science and Technology, 2019)
Collagen extracted from the skin of fan-bellied leatherjacket was hydrolyzed and tested for antioxidant activity. The yields of acid soluble collagen (ASC) and pepsin soluble collagen (PSC) were 14.8% and 19.6%, respectively, based on the wet weight of skin. The SDS-PAGE results showed that collagen from the skin of this fish consists of α1 and α2 chains with molecular weight (MW) approximately 100 kDa, identified as type I collagen. Hydrolysis of collagen by the other enzymes, such as papain, bromelain, pepsin and alcalase could produce the peptides with MW less than 28 kDa. Hydrolyzed collagen possessed the antioxidant activity with different levels and greater than that of normal collagen.